The Role of Antioxidants in Preventing Chronic Kidney Disease Progression: Mechanisms and Clinical Implications - Malik, Rida; Sikander, Suleman; Qadir, Jalil; Ahmed, Muzzamil; Habib, Muhammad Kashif; Mustafa, Hibah Adnan (Indus Journal of Bioscience Research, 2025)
This study aims to investigate the determinants of the progression of Chronic Kidney Disease (CKD) and the role of antioxidant supplementation in managing oxidative stress and kidney function. The research used a cross-sectional study with 120 participants, considering variables such as age, gender, smoking, family history, diet, alcohol consumption, education, and occupation. Key findings from the analysis were that age was a significant contributing factor to CKD progression, with older individuals having greater likelihood of developing advanced disease stages. Males, particularly those with hypertension, had increased prevalence of kidney damage. Smoking was also found to accelerate CKD progression, with intake of a diet rich in fruits and vegetables being associated with high antioxidant use. The intervention group, supplemented with antioxidants, evidenced remarkable reductions in indicators of oxidative stress as well as improvement of kidney function compared to existing levels, as shown by statistical comparison through Paired t-tests and Wilcoxon Signed-Rank Tests (p < 0.05). The control group, on the other hand, experienced no similar significant alterations. In addition, a multivariable regression model proved the impact of age, baseline kidney function, and comorbid illness on CKD outcomes with poorer outcomes in older patients and reduced baseline eGFR. The findings suggest that lifestyle modifications such as smoking abstinence and diet change, and antioxidant supplementation may have a significant role in CKD progression and oxidative stress and are potential targets for clinical intervention. This study highlights key determinants influencing Chronic Kidney Disease (CKD) progression, emphasizing modifiable risk factors like smoking, diet, alcohol use, and physical activity. Findings support antioxidant supplementation and lifestyle modifications as crucial strategies for slowing CKD progression and improving renal health outcomes.